Pengaruh Pemberdayaan dan Kepuasan Kerja terhadap Kinerja Dosen di Universitas Majalengka Jawa Barat - Dita Cucu Kartika; Ma'ruf Akbar; Rugaiyah Rugaiyah (Universitas Indraprasta PGRI Jakarta, 2018)
The objective of this research is to comprehensively understand the effect of empowerment and job satisfaction on the job performance of lecturer in Universitas Majalengka, West Java. The research uses a survey method with path analysis technique by distributing questionnaires as a research instrument. 80 respondents are involved by writing their feedback on the questionnaires. Those respondents are selected applying Simple Random Sampling among all lecturers working at Universitas Majalengka. The results of research, analysis and interpretation reveal that (1) empowerment has a direct positive effect on job performance, (2) job satisfaction has a direct positive effect on job performance, (3) empowerment has a direct positive effect on job satisfaction.